Improvement of Public Awareness on Fasciolosis as Zoonosis Disease - Martindah, Eny; Widjajanti, S; Estuningsih, S E; ., Suhardono (Indonesian Bulletin of Animal and Veterinary Sciences, 2005)
Fasciolosis is commonly suffered by the ruminants such as cattle and buffaloes, and as one of the most important parasitic disease . The prevalence of fasciolosis in ruminants is related to the contaminated feedstuff and water supply with metacercariae, the infective larvae of trematode genus Fasciola spp ., such as Fasciola gigantica and F. hepatica. In Indonesia, the prevalence of this disease in ruminants could be up to 90%, and there is no case report on human being . However, the occurrence of this disease in human should be anticipated, since many cases have been reported in human in the other countries, such as South America, Europe, Australia, New Zealand and South East Asia (Thailand and Vietnam), as "Food-borne infection" and as one of the most important issues in public health . Ironically, the farmers and the extension agents in Indonesia do not aware on the danger of this disease neither to the animals nor to human, so they also do not care on how to prevent and control the disease. This phenomenon appears maybe because fasciolosis is a chronic disease without any significant clinical signs and quite difficult to be detected . Thus, it is very important to improve the public awareness on fasciolosis both in ruminants and its possibility in human being . The endemic areas can be defined by epidemiological surveillance using accurate early diagnostic test, so that strategic and sustainable fasciolosis control in the endemic areas could be implemented . This program will be succeeded if there is strong integrated collaboration among the farmers, the extension agents, the researchers and the decision makers in the related departments . Key words : Fasciolosis, zoonosis, public awareness